Clinical outcome in anti-neutrophil cytoplasmic antibody–associated vasculitis and gene variants of 11β-hydroxysteroid dehydrogenase type 1 and the glucocorticoid receptor. (14th November 2018) - Hessels, Arno C; Tuin, Janneke; Sanders, Jan Stephan F; Huitema, Minke G; van Rossum, Elisabeth F C; Koper, Jan W; van Beek, André P; Stegeman, Coen A; Rutgers, Abraham
Abstract: Objectives: We aimed to investigate whether five potential functional haplotypes of the glucocorticoid receptor ( GR ) gene and a single-nucleotide polymorphism of 11β-hydroxysteroid dehydrogenase type 1 ( HSD11B1 ) are associated with clinical outcome in ANCA-associated vasculitis. Methods: Patients diagnosed with ANCA-associated vasculitis ( n = 241) were genotyped for five polymorphisms of the GR gene and one polymorphism of the HSD11B1 gene. GR gene haplotypes were predicted based on genotyping results. Relapse-free survival, mortality, renal survival, metabolic adverse events and infections were compared between carriers and non-carriers of GR haplotypes and the HSD11B1 genotype. Results: Carriers of haplotype 4 (ER22/23EK + 9β+TthIII1) of GR had a significantly higher 5-year mortality risk [hazard ratio (HR) 4.5 (95% CI 1.6, 12.8)] and had a higher risk of developing end-stage renal disease [HR 7.4 (95% CI 1.9, 28.7)]. Carriers of a minor variant of HSD11B1 more frequently experienced relapse [HR 2.5 (95% CI 1.5, 4.1)] except if they also carried haplotype 1 ( Bcl I) of GR . Homozygous carriers of haplotype 1 had a higher risk of developing dyslipidaemia [HR 4.1 (95% CI 1.8, 9.6)]. The occurrence of infections did not differ between GR haplotypes and HSD11B1 genotypes. Conclusion: Haplotypes 1 and 4 of GR and a polymorphism of the HSD11B1 gene were associated with clinically relevant inflammatory and metabolic outcomes in ANCA-associated vasculitis.